Síndrome coronario crónico: decisión diagnóstico-terapéutica - Ana Karen Torres Palma; Maria José Pacheco Coello; Hector Marcelo Hachi Powel; José Antonio Valdiviezo Flores; Edson Ricardo Condo Borja (Correo Científico Médico, 2023)
RESUMEN